Adaptive Working Memory Training and Functional Outcomes Post-Stroke: A Randomized Trial - Daniel Alfredo Landínez Martínez; David Montoya-Arenas; Alejandra Arboleda-Ramirez; José Franco Vásquez (Mediterranean Journal of Clinical Psychology, 2024)
Background: Cognitive deficits following ischemic stroke significantly impair functional independence, particularly in instrumental activities of daily living. Previous research highlights working memory as a key target for rehabilitation, but the effectiveness of adaptive working memory training in improving functional outcomes remains underexplored. This study draws on the theoretical framework linking cognitive reserve and neuroplasticity to post-stroke recovery, hypothesizing that targeted cognitive interventions can enhance both working memory and instrumental activities of daily living performance.